Implementasi Model Pembelajaran Savi (Somatis-Auditori-Visual-Intelektual) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran PAI di SMP N 6 Lubuklinggau - Akip, Muhamad; Khasanah, Nevi Laila; Rahmawati, Asih (Edification Journal : Pendidikan Agama Islam, 2022)
The purpose of this study was to determine the application of the SAVI (Somatic-Auditory-Visual-Intellectual) learning model to the PAI learning outcomes of students at SMP N 6 Lubuklinggau. The research method used is a quantitative research method with hypothesis testing using the SPSS 17.0 application. In this study, and conducted more than one test at the beginning (Pretest) and carried out at the end (Posttest). The test used is a paired sample statistical test with a significance level of 0.05. The results showed that the t count (8.787) was greater than the t table (2.228) and the value of Sig. (2-tailed) (0.00) is smaller than the probability (0.05) so it can be concluded that Ha is accepted and Ho is rejected. This means that there is a significant influence between the SAVI learning model on the learning outcomes of class VIII students of SMP N 6 Lubuklinggau. The results also showed that the increase in student learning outcomes after being given treatment using the SAVI learning model was in the medium category.